Other paths of Clio: The representations of cities in Piauí in the work Caatingas e Chapadões, by Francisco de Assis Iglésias (1912-1919) - Nascimento , Gustavo Cleon Marques; Filho, Pedro Pio Fontineles (Seven Editora, 2024)
The main objective of this work is to understand the representations of the cities of Piauí in the years 1912-1919 described by Francisco de Assis Iglésias in his work "Caatingas e Chapadões", 1953. Thus, some specific objectives are pertinent to the research, such as: discussing the (auto)biographical and memorialistic traits of the writer in his narrative; infer about the relationships between the notions of space and spatialities, time and temporalities in the writer’s work; analyze the narrative of the book Caatinga and Chapadões in its approximations and distances between History, Memory and Literature. Therefore, as a methodological framework, the work is analyzed together with theoretical-methodological readings on the main axes of inference, literature, memory and city essential for a satisfactory exploration of the research. In order to deepen these academic branches, it is necessary to read authors such as Marc Bloch (1997), Euclides da Cunha (1984), Peter Burke (1992), Raymond Williams (1989), Ítalo Calvino (2003), Pedro Pio Fontineles Filho (2008), Teresinha Queiroz (1994), Erisvaldo Fagundes (2015) and Durval Muniz (2018). author’s view, since his book is the main source of this research. In the meantime, the previous consideration points out that the research reconstructs the spaces traversed by Iglésias, presenting the conditions present at the time that make up the cities and culture of Piauí. The memory of these scenarios preserves their strangeness and representations in relation to the landscapes of cities such as Teresina, Parnaíba, Uruçuí and Floriano. Thus, "Caatingas e Chapadões" constitutes a place of memory, a rich source for historical research, which brings a romanticized narrative, which transcends the technical content of an agronomist, as it has as its background the urban, the rural, the cultures and political issues present at the beginning of the twentieth century. DOI:https://doi.org/10.56238/sevened2024.007-090